2014
DOI: 10.1080/10556788.2013.877905
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral approximations inp-order cone programming

Abstract: This paper discusses the use of polyhedral approximations in solving p-order cone programming (pOCP) problems, or linear problems with p-order cone constraints, and their mixed-integer extensions. In particular, it is shown that the cutting-plane technique proposed in Krokhmal and Soberanis [Risk optimization with p-order conic constraints: A linear programming approach, Eur. J. Oper. Res. 201 (2010), pp. 653-671, http://dx.] for a special type of polyhedral approximations of pOCP problems, which allows for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Note that it has been previously observed (see, Vielma et al (2008); Vinel and Krokhmal (2014b) and Chapter 3 of the current work) that ε 1 can be selected to be relatively large and still provide promising computational results, which explains the relation ε 2 ε 1 above. Note also that in this case, the described procedure can be viewed as repetitive resolving of a relatively small-scale LPs due to P 1 , guided by a regular branch-and-bound, with occasional calls to a large-scale P 2 .…”
Section: Branch-and-bound Methodssupporting
confidence: 65%
“…Note that it has been previously observed (see, Vielma et al (2008); Vinel and Krokhmal (2014b) and Chapter 3 of the current work) that ε 1 can be selected to be relatively large and still provide promising computational results, which explains the relation ε 2 ε 1 above. Note also that in this case, the described procedure can be viewed as repetitive resolving of a relatively small-scale LPs due to P 1 , guided by a regular branch-and-bound, with occasional calls to a large-scale P 2 .…”
Section: Branch-and-bound Methodssupporting
confidence: 65%
“…Thus, in addition to the SOCP-based approaches for solving the pOCP problem (28) discussed earlier, we also employ an exact polyhedral-based approach with O −1 iteration complexity that was proposed in Vinel and Krokhmal (2014c). It consists in reformulating the p-order cone w 0 ≥ w 1 w N p via a set of three-dimensional p-cones…”
Section: Socp Reformulation Of P-ordermentioning
confidence: 99%
“…The process is initialized with j = 1 , 1 = /4, j = 1 N − 1, and continues until no violations of condition (35) are found. In Vinel and Krokhmal (2014c), it was shown that this cuttingplane procedure generates an -approximate solution to pOCP problem (28) within O −1 iterations.…”
Section: Socp Reformulation Of P-ordermentioning
confidence: 99%
See 1 more Smart Citation
“…We mention an important way of constructing polyhedral approximations to the second-order cone is proposed by Ben-Tal and Nemirovski in [7], which exploits rotational symmetry. This approximation is first applied to MISOCP in [47] and further studied in [49].…”
Section: (Miqcp)mentioning
confidence: 99%